2003
DOI: 10.1046/j.1365-2826.2003.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

MT1 Melatonin Receptor mRNA Expressing Cells in the Pars Tuberalis of the European Hamster: Effect of Photoperiod

Abstract: Melatonin, secreted only during the night by the pineal gland, transduces the photoperiodic message to the organism. One important target for the hormone is the pars tuberalis (PT) of the adenohypophysis which displays a very high number of melatonin binding sites in mammals and is implicated in the seasonal regulation of prolactin secretion. To gain insight into the mechanism by which the melatonin signal is decoded in the PT, we studied the effect of photoperiod on the PT cells expressing the MT1 melatonin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 57 publications
8
87
0
1
Order By: Relevance
“…Melatonin receptors are highly expressed in the PT (Dardente et al 2003), which is consistent with the notion that melatonin mediates photoperiodic information. LD stimuli induce DIO2 expression in ependymal cells in hamsters (Watanabe et al 2004).…”
Section: Regulatory Mechanism For Mammalian Seasonal Reproductionsupporting
confidence: 85%
“…Melatonin receptors are highly expressed in the PT (Dardente et al 2003), which is consistent with the notion that melatonin mediates photoperiodic information. LD stimuli induce DIO2 expression in ependymal cells in hamsters (Watanabe et al 2004).…”
Section: Regulatory Mechanism For Mammalian Seasonal Reproductionsupporting
confidence: 85%
“…Annual variation in melatonin signal duration has been shown to be a critical input signal for the annual timing mechanism [81,82] that involves the pituitary and its pars tuburalis (PT), which is densely packed with melatonin receptors [83][84][85][86][87][88][89]. Pineal melatonin release is driven by the SCN via the paraventricular nucleus (PVN), superior cervical ganglion (SCG) and intermediolateral column of the spinal cord (IML) pathway [58,69].…”
Section: Adjustment To Changing Day Length As a Selection Force For Tmentioning
confidence: 99%
“…There are two major subtypes of mammalian melatonin receptor, termed MT 1 and MT 2 (previously Mel 1a and Mel 1b ; reviewed in Reppert et al (1996)), of which MT 1 is the dominant pituitary subtype (Weaver et al 1996, von Gall et al 2002. Despite transient expression of MT 1 receptors in neonatal pituitary gonadotrophs (Johnston et al 2003b), co-localisation studies have shown that MT 1 is only expressed in the PT-specific thyrotroph cells in adult rodents (Klosen et al 2002, Dardente et al 2003.…”
Section: The Pars Tuberalis (Pt) and Tuberalinmentioning
confidence: 99%